Optimized Diazo Scaffold for Protein Esterification - Mix, Kalie A. (Org Lett, 2015)
[Image: see text] The O-alkylation of carboxylic acids with diazo compounds provides a means to esterify carboxylic acids in aqueous solution. A Hammett analysis of the reactivity of diazo compounds derived from phenylglycinamide revealed that the p-methylphenylglycinamide scaffold has an especially high reaction rate and ester:alcohol product ratio, and esterifies protein carboxyl groups more efficiently than does any known reagent.